2022
DOI: 10.3130/aijt.28.121
|View full text |Cite
|
Sign up to set email alerts
|

Development of Substructure Real-Time Online Testing System for Seismically Isolated Building With a Small Response Delay Using Existing Experimental Equipment

Abstract: This paper describes development of substructure real-time online response testing system (SROLT) for seismically isolated building with a small response delay using existing experimental equipment. Authors made analytical examinations of the influence of response delay to the test results caused by using existing experimental equipment, and developed a control method to minimize the problem. It was demonstrated by various test results that the developed system has sufficient accuracy as SROLT for seismically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Therefore, the SROLT system is an appropriate system for confirming the accuracy of the hysteresis model of RBs, as the behavior of RBs is evaluated using an actual test specimen. The authors have verified the accuracy of the SROLT system 25 . In this study, the accuracy of the proposed DHI model was confirmed by comparing the results of the SROLT.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…Therefore, the SROLT system is an appropriate system for confirming the accuracy of the hysteresis model of RBs, as the behavior of RBs is evaluated using an actual test specimen. The authors have verified the accuracy of the SROLT system 25 . In this study, the accuracy of the proposed DHI model was confirmed by comparing the results of the SROLT.…”
Section: Introductionmentioning
confidence: 52%
“…The authors have verified the accuracy of the SROLT system. 25 In this study, the accuracy of the proposed DHI model was confirmed by comparing the results of the SROLT.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations